1999
DOI: 10.1021/bi991765q
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Radii of Native and Denatured Proteins Measured by Pulse Field Gradient NMR Techniques

Abstract: Pulse field gradient NMR methods have been used to determine the effective hydrodynamic radii of a range of native and nonnative protein conformations. From these experimental data, empirical relationships between the measured hydrodynamic radius (R(h)) and the number of residues in the polypeptide chain (N) have been established; for native folded proteins R(h) = 4.75N (0.29)A and for highly denatured states R(h) = 2.21N (0.57)A. Predictions from these equations agree well with experimental data from dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

154
1,044
5
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 943 publications
(1,211 citation statements)
references
References 56 publications
154
1,044
5
8
Order By: Relevance
“…Another recent study using FCS reported in contrast a hydrodynamic radius of Aβ1-40 and Aβ1-42 as small as 0.85-0.9 nm 25 . Such a value deviates significantly from the above estimates of R h as well as from other proteins of similar sizes 22,26 , and is only about 50% larger than that of the fluorophore Rhodamine B to which Aβ was coupled (R h =0.57 nm) 25 .…”
Section: Discussioncontrasting
confidence: 72%
“…Another recent study using FCS reported in contrast a hydrodynamic radius of Aβ1-40 and Aβ1-42 as small as 0.85-0.9 nm 25 . Such a value deviates significantly from the above estimates of R h as well as from other proteins of similar sizes 22,26 , and is only about 50% larger than that of the fluorophore Rhodamine B to which Aβ was coupled (R h =0.57 nm) 25 .…”
Section: Discussioncontrasting
confidence: 72%
“…This is put into evidence, for example, by the data on hydrodynamic radii and radii of gyration of chemically denatured proteins. [9][10][11] The random-coil-like behavior of unfolded proteins has been sometimes underappreciated, since much (deserved) attention has been given to the investigation of residual structure. It is this category of proteins, where disorder prevails over order, which is the focus of the present article.…”
Section: Introductionmentioning
confidence: 99%
“…Using intrinsic viscosity measurements for 12 proteins denatured by 5-6 M GuHCl, the authors obtained a scaling exponent ν=0.67±0.09. Wilkins et al [191] showed that the hydrodynamic radii of sets of 8 highly denatured, disulfide-free proteins follow a power law scaling with ν=0.58±0.11. Recently, Kohn et al [192] reassessed the scaling behavior of denatured proteins using small angle x-ray scattering for 17 proteins of lengths varying from 8 to 549 residues.…”
Section: Unfolded Protein Statesmentioning
confidence: 99%